2005
DOI: 10.1128/jb.187.3.912-922.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation ofsitABCDofSalmonella entericaSerovar Typhimurium by MntR and Fur

Abstract: Salmonella enterica serovar Typhimurium has two manganese transport systems, MntH and SitABCD. MntH is a bacterial homolog of the eukaryotic natural resistance-associated macrophage protein 1 (Nramp1), and SitABCD is an ABC-type transporter. Previously we showed that mntH is negatively controlled at the transcriptional level by the trans-acting regulatory factors, MntR and Fur. In this study, we examined the transcriptional regulation of sitABCD and compared it to the transcriptional regulation of mntH by cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 40 publications
10
113
0
Order By: Relevance
“…As previously demonstrated (22,26,28,38), we observed that mntH is repressed by manganese and induced by EDTA (Fig. 2).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As previously demonstrated (22,26,28,38), we observed that mntH is repressed by manganese and induced by EDTA (Fig. 2).…”
Section: Resultssupporting
confidence: 87%
“…Upon binding to manganese, MntR binds promoter DNA to repress or activate transcription of its target genes (15,30). In enterobacteria, the only genes known to be regulated by MntR when this work began were mntH and sitABCD, encoding manganese transporters, of which laboratory strains of Escherichia coli only possess mntH (22,26,38). In some Gram-positive bacteria, the MntR analog seems to regulate a large set of genes and mediate a more global response (36).…”
mentioning
confidence: 99%
“…6B) suggests that Fe also plays a role in the Mn homeostasis. Similar Mn-mediated activation of Fur-and Fe-mediated activation of MntR was also observed earlier (10,35,36). Our data also suggest that the MntRFe 2ϩ complex is able to suppress mntH expression (see Fig.…”
Section: A Robust Link Between Hflx and Mn Homeostasis Is Discoveredsupporting
confidence: 73%
“…However, alternative mechanisms of regulation, viz. Mn-mediated activation of Fur, Fe-mediated activation of MntR, or Mnmediated inactivation of Zur, have also been proposed (10,30,34,35,36). In our present study, accumulation of Mn in the Mnperturbed ⌬hflX strain increases Zn and decreases Fe levels, suggesting that an influx of Mn is capable of affecting both Fe and Zn regulatory networks (Fig.…”
Section: Fig 3 Hflx-mediated Mn Homeostasis Is Not Linked To the Mntrsupporting
confidence: 53%
“…In view of this, we must consider that other Fur-regulated genes, namely those with complex regulation involving additional factors, may not have been identified in these studies. Reports for other organisms have described a number of regulatory circuits that respond to changes in iron levels, including the stringent control pathways (72) and those involving Crp (83) or the manganese regulator MntR (38,40). These networks could potentially influence the iron-dependent Fur regulon in V. cholerae.…”
Section: Discussionmentioning
confidence: 99%